Association of socioeconomic disadvantage with operative outcomes for infective endocarditis - Barzin Badiee; Sara Sakowitz; Saad Mallick; Nguyen Le; Arjun Chaturvedi; Kevin Tabibian; Esteban Aguayo; Peyman Benharash (PLoS ONE, 2025)
Background Social determinants of health (SDOH) are well-recognized contributors of disparities in cardiovascular disease. Yet, the association of socioeconomic disadvantage with outcomes following operative management of infectious endocarditis (IE) remains ill-defined. Methods Nonelective adult (≥18 years) hospitalizations entailing cardiac valve operations for IE were tabulated from the 2016–2021 Nationwide Readmissions Database. Those facing adverse SDOH, including compromised economic, educational, healthcare, environmental, and social conditions, were categorized as Disadvantaged (others: Non-Disadvantaged). Multivariable regression models were developed to examine the association of socioeconomic disadvantage with key endpoints. Results Of an estimated 36,527 hospitalizations, 31.9% were categorized as Disadvantaged with the proportion increasing from 27.0% in 2016 to 34.8% in 2021 (P < 0.001). On average, Disadvantaged was younger (50 [34–64] vs 53 years [37–65], P < 0.001), more frequently insured by Medicaid (33.8 vs 26.4%, P < 0.001), and more commonly underwent isolated tricuspid operations (21.9 vs 13.7%, P < 0.001). Following risk adjustment, Disadvantage remained linked with significantly greater likelihood of acute kidney injury (Adjusted Odds Ratio [AOR] 1.20, 95% Confidence Interval [CI] 1.12–1.29), stroke (AOR 1.25, 95%CI 1.11–1.41), and prolonged mechanical ventilation ≥24 hours (AOR 1.80, 95%CI 1.65–1.96). Further, Disadvantaged was associated with incremental increases in postoperative hospitalization duration (+4.97 days, 95%CI 4.39–5.54) and costs (+$32,900, 95%CI $29,300−36,500) as well as a greater risk of nonelective 90-day readmissions (AOR 1.12, 95%CI 1.03–1.23). Conclusions Adverse SDOH are independently linked with greater morbidity and resource utilization following surgical management of IE. Efforts are needed to ensure comprehensive SDOH screening upon admission and develop targeted in-hospital interventions to address persistent disparities.